2011
DOI: 10.1007/s00213-011-2171-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of scopolamine and biperiden as a rodent model for cholinergic cognitive impairment

Abstract: RationaleThe nonselective muscarinic antagonist scopolamine hydrobromide (SCOP) is employed as the gold standard for inducing memory impairments in healthy humans and animals. However, its use remains controversial due to the wide spectrum of behavioral effects of this drug.ObjectiveThe present study investigated whether biperiden (BIP), a muscarinic m1 receptor antagonist, is to be preferred over SCOP as a pharmacological model for cholinergic memory deficits in rats. This was done by comparing the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
4
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 114 publications
(162 reference statements)
1
41
4
1
Order By: Relevance
“…As a result, the use of BIP is expected to induce cognitive deficits such as impaired learning and memory without serious peripheral effects [9]. Klinkenberg and Blokland [7] confirmed these expectations in rats.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…As a result, the use of BIP is expected to induce cognitive deficits such as impaired learning and memory without serious peripheral effects [9]. Klinkenberg and Blokland [7] confirmed these expectations in rats.…”
Section: Introductionmentioning
confidence: 78%
“…Scopolamine, a non-selective muscarinic antagonist, has become the gold standard for inducing AD-like cognitive deficits pharmacologically [1,2]. This compound, however, may induce many peripheral effects (see [2,7,8]) which can bias the results [2,7]. It has been suggested that the anticholinergic drug biperiden (BIP) represents an alternative.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pharmacologic imaging studies, electrophysiologic studies, and behavioral animal studies further support a role for M 1 Rs in learning and memory (14)(15)(16). In this regard, recently developed drugs selectively targeting M 1 R, including M 1 agonists and positive allosteric modulators, have helped to further define the role of this receptor subtype in cognition (5,(8)(9)(10), providing further impetus for clinical development of therapies for diseases associated with cognitive deficits.…”
mentioning
confidence: 94%
“…The scopolamine model is used extensively for preclinical testing of new substances designed to treat cognitive impairment [9].…”
Section: Introductionmentioning
confidence: 99%